2016
DOI: 10.1002/ecs2.1242
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based evaluation of the cumulative effects of ecosystem restoration

Abstract: Abstract. This study adapts and applies the evidence-based approach for causal inference, a medical standard, to the restoration and sustainable management of large-scale aquatic ecosystems. Despite long-term investments in restoring aquatic ecosystems, it has proven difficult to adequately synthesize and evaluate program outcomes, and no standard method has been adopted. Complex linkages between restorative actions and ecosystem responses at a landscape scale make evaluations problematic and most programs foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 105 publications
0
45
0
Order By: Relevance
“…These indirect and cross‐boundary effects (CEQ , Diefenderfer et al. ) occurred throughout the floodplain riverscape. The modeling showed that the new culverts, as well as a flood event that overtopped the levee, were important conduits for the exchange of a large mass of organic material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These indirect and cross‐boundary effects (CEQ , Diefenderfer et al. ) occurred throughout the floodplain riverscape. The modeling showed that the new culverts, as well as a flood event that overtopped the levee, were important conduits for the exchange of a large mass of organic material.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers measured the responses of tidal wetlands to tidal hydrological reconnection, and developed and implemented methods for predicting the effects of multiple restoration projects on the ecosystem (Diefenderfer et al. , , Ke et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is something of a quiet revolution that will not be televised but likely discussed at every restoration and conservation meeting worldwide. People need nature for health and well‐being directly (Berman et al ; Louv ; McMahan & Estes ; Kuo et al ), for landscape‐level maintenance of simple cumulative effects of relatively more natural processes (Diefenderfer et al ), and for the cultural benefits that we derive from a sense of place and access to open areas (Tew et al ). Nonetheless, we live in a time when nature needs us (Dalby ), and our work will never be done.…”
Section: Strategic Issuesmentioning
confidence: 99%
“…Defining restoration outcomes is nontrivial and will continue to be a challenge (Diefenderfer et al ; Svejcar & Kildisheva ; Gellie et al ; Henry et al ). Several novel thinking themes were proposed at the meeting.…”
Section: Strategic Issuesmentioning
confidence: 99%